Contexto geológico e estrutural do Maciço Rio Apa, sul do Cráton amazônico - MS - Godoy, Antonio Misson [UNESP]; Manzano, Jefferson Cassu [UNESP]; de Araújo, Larissa Marques Barbosa; da Silva, Jesué Antonio (My University, 2009)
Rio Apa Massif crops out in the Mato Grosso do Sul state and corresponds to the southeastern portion of the Amazonian Craton dominantly Paleoproterozoic in age. Rio Apa Complex is oldest and it is composed mainly by migmatitic orthogneisses, beyond amphybolites, tonalities and granodiorite. Alto Tererê Group is composed by schists, biotitemuscovite gneisses and micaceous quartzites generally rich in garnets, beyond metabasic rocks of low amphibolite facies. The Amoguijá Group is constituted by Alumiador Intrusive Suite, which is represented by a sieno to monzogranitic batholith and Serra da Bocaina Volcanic Suite composed of volcanoclastic rocks of alkali riolites to monzoriolites compositions and pyroclastic products. Overlaying towards East and South occurs Neoproterozoic metasedimentary rocks from the Paraguai Folded Belt (Cuiabá, Corumbá and Jacadigo Groups - Urucum Formation). Structural-metamorphic framewok is identified by five deformational phases but the actual tectonic and metamorphic structure shows the superposed tectonic array of the Paraguai Folded Belt. Rocks from Rio Apa Complex, Alto Tererê Group and Amoguijá Group record an older structural evolution defined by (Dn-1 and Dn). The deformational phases (Dn+1 and Dn+2) are visible mainly in rocks of Paraguai Folded Belt beyond the last deformation (Dn+3) that imprints all sequences.

O Maciço do Rio Apa ocorre no sudoeste do estado de Mato Grosso do Sul e corresponde à porção meridional do Cráton Amazônico de idade dominantemente Paleoproterozóica. O Complexo Rio Apa, mais antigo, é constituído por ortognaisses migmatíticos, além de anfibolitos, tonalitos e granodioritos. O Grupo Alto Tererê é composto por xistos, biotita - muscovita gnaisses e quartzitos micáceos, comumente granatíferos, além de rochas metabásicas, em fácies anfibolito baixa. O Grupo Amoguijá é definido pela Suíte Intrusiva Alumiador que representa um batólito de composição sieno a monzogranítica e pela Suíte Vulcânica Serra da Bocaina composta por rochas vulcanoclásticas de composição álcali - riólito a monzoriólitos e produtos piroclásticos. Sobreposta, a leste e a sul ocorrem as rochas metassedimentares Neoproterozóicas da Faixa de Dobramento Paraguai (grupos Cuiabá, Corumbá e Jacadigo – Formação Urucum). O quadro estrutural - metamórfico é identificado por 5 fases deformacionais, mas sua atual estruturação tectônica - metamórfica passa pelo arranjo tectônico superimposto da Faixa de Dobramentos Paraguai. As rochas do Complexo Rio Apa, Grupo Alto Tererê e Grupo Amoguijá registram uma evolução estrutural reliquiar antiga definida pelas fases (Dn-1 e Dn). As fases deformacionais (Dn+1 e Dn+2) encontram-se visíveis principalmente nas rochas da Faixa de Dobramento Paraguai, enquanto deformações (Dn+3) superimpõem a todas as sequências. Palavras-chave: Maciço Rio Apa, Cráton Amazônico, petrografia, evolução estrutural.
Geological and structural frame of the Rio Apa Massif, southeastern of the Amazonian Craton (MS), Brasil
Keywords: Amazonian craton; Petrography; Rio apa massif; Structural evolution; amphibolite; batholith; craton; metasedimentary rock; migmatization; orthogneiss; petrography; pyroclastic deposit; schist; tonalite; volcaniclastic deposit; Brazil; Mato Grosso do Sul